Mastering MEAN web development - Madera, Luke; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2015)
"Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. This video course uses real-time examples to get you started with writing high quality code that could actually be used in production applications, just like a seasoned developer. You can follow along in the code text editor and see live changes in the web browser. If you want to learn to code with modern technologies to build websites and cross-platform mobile applications using just one language (full stack JavaScript) from frontend to backend, this course is for you. You just need a quick run through your JavaScript and NoSQL notes and you are ready to go."--Resource description page.
Title from resource description page (viewed May 19, 2015)
Date of publication taken from resource description page.
Presenter, Luke Madera.
Keywords: Web site development; MongoDB; EXPRESS (Computer program language); AngularJS (Software framework); Node.js.; Electronic books